1977
DOI: 10.1177/001100007700600428
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Research in Carkhuff's Human Resource Development Training Programs: Where is the Donut?

Abstract: This paper presents a critical review of research which has been offered in support of training programs that focus on Human Relations Development as proposed by Robert Carkhuff. The studies relied upon by Carkhuff and his students have failed to specify the nature of treatment; its components seem to vary from one study to the next; control groups of a comparative type are usually missing and, when present, have not been equivalent in expectation, motivation, contact time, leader skill or enthusiasm. Measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

1978
1978
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…It is particularly unfortunate that many counselor educators have not differentiated between his conceptual-based training model and his revised skill-based training model. After the many criticisms of Carkhuff's pre-1974 training model (Gormally & Hill, 1974;Lambert & DeJulio, 1977;Lambert, DeJulio, & Stein, 1978;Mahon & Altmann, 1977), it seems that many counselor educators have ignored the revised training technology and have discontinued research on its potential effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…It is particularly unfortunate that many counselor educators have not differentiated between his conceptual-based training model and his revised skill-based training model. After the many criticisms of Carkhuff's pre-1974 training model (Gormally & Hill, 1974;Lambert & DeJulio, 1977;Lambert, DeJulio, & Stein, 1978;Mahon & Altmann, 1977), it seems that many counselor educators have ignored the revised training technology and have discontinued research on its potential effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical studies of empathy have been reviewed in various publications (see e.g. [2][3][4][5][6][7][8][9][10][11][12][13]). However, after reading publications in which empirical research on medical students' or physicians' empathy has been presented or discussed, my impression was that important methodological assumptions, ideals, and trends did not receive adequate attention.…”
Section: Introductionmentioning
confidence: 99%
“…This view is generally supported by Lambert and DeJulio (1977) in their critical review of research that was offered in support of training programs that focus on human relations development as the central thrust. The major problem continues to be the lack of agreement on what characterizes the "effective" trainee as well as the role of the client's and supervisor's behavior in influencing the growth and development of the counselor trainee.…”
mentioning
confidence: 99%
“…Second, in a review of research on the relationship between empathy and counseling outcome, Gladstein (1977) suggested that "due to the lack of clear evidence, counselor preparation programs should be more cautious in emphasizing the role of empathy in counseling" (p. 77). This view is generally supported by Lambert and DeJulio (1977) in their critical review of research that was offered in support of training programs that focus on human relations development as the central thrust. The major problem continues to be the lack of agreement on what characterizes the "effective" trainee as well as the role of the client's and supervisor's behavior in influencing the growth and development of the counselor trainee.…”
mentioning
confidence: 99%